Clinical evaluation of the proximal femur intramedullary nail antirotation system-II for treatment of unstable pertrochanteric fractures - Avtar, Ram; Gupta, Rajat (International Journal of Research in Orthopaedics, 2019)
Background: Pertrochanteric fractures are relatively common among the elderly. Common techniques for fixation of these fractures are sliding hip screw and plate or intramedullary nailing. The objective of the present study was designed to evaluate and analyze the role of proximal femoral nail antirotation II (PFNA II) in the treatment of unstable pertrochanteric fractures. Methods: It was a prospective study on 50 cases of unstable pertrochanteric fractures. Harris hip score was used for functional assessment. Results: In this study at 6 months follow up, Union was achieved in 48 cases, technical and mechanical complications were noted in 6% cases (3 cases). Reoperation rate was 4% (2 cases). According to Harris Hip scoring system Excellent results were noted in 26 cases, good in 14 cases, fair in 8 cases and poor result in 2 cases. Conclusions: It is concluded from our study that PFNA II is an attractive and suitable implant for unstable pertrochanteric fractures.